Genomewide profiling of copy-number alteration in monoclonal gammopathy of undetermined significance - Mikulasova, Aneta; Smetana, Jan; Wayhelova, Marketa; Janyskova, Helena; Sandecka, Viera; Kufova, Zuzana; Almasi, Martina; Jarkovsky, Jiri; Gregora, Evzen; Kessler, Petr; Wrobel, Marek; Walker, Brian A; et al. (European journal of haematology, 2016)
Monoclonal gammopathy of undetermined significance (MGUS) is a benign condition with an approximate 1% annual risk of symptomatic plasma cell disorder development, mostly to multiple myeloma (MM). We performed genomewide screening of copy-number alterations (CNAs) in 90 MGUS and 33 MM patients using high-density DNA microarrays. We identified CNAs in a smaller proportion of MGUS (65.6%) than in MM (100.0%, P = 1.31 × 10-5 ) and showed median number of CNAs is lower in MGUS (3, range 0-22) than in MM (13, range 4-38, P = 1.82 × 10-10 ). In the MGUS cohort, the most frequent losses were located at 1p (5.6%), 6q (6.7%), 13q (30.0%), 14q (14.4%), 16q (8.9%), 21q (5.6%), and gains at 1q (23.3%), 2p (6.7%), 6p (13.3%), and Xq (7.8%). Hyperdiploidy was detected in 38.9% of MGUS cases, and the most frequent whole chromosome gains were 3 (25.6%), 5 (23.3%), 9 (37.8%), 15 (23.3%), and 19 (32.2%). We also identified CNAs such as 1p, 6q, 8p, 12p, 13q, 16q losses, 1q gain and hypodiploidy, which are potentially associated with an adverse prognosis in MGUS. In summary, we showed that MGUS is similar to MM in that it is a genetically heterogeneous disorder, but overall cytogenetic instability is lower than in MM, which confirms that genetic abnormalities play important role in monoclonal gammopathies.
Keywords: Disease Progression; srovnávací genomová hybridizace; celogenomová asociační studie; Multiple Myeloma; prognosis; nestabilita genomu; genomika; DNA microarrays; progrese nemoci; Monoclonal Gammopathy of Undetermined Significance; DNA Copy Number Variations; mužské pohlaví; Comparative Genomic Hybridization; mnohočetný myelom; monoklonální gamapatie nejasného významu; ženské pohlaví; monoclonal gammopathies; Genomics; Humans; DNA copy-number changes; Genomic Instability; Chromosome Aberrations; chromozomální aberace; variabilita počtu kopií segmentů DNA; Female; Genome-Wide Association Study; lidé; Male